Analysing effective thermal conductivity of 2D closed-cell foam based on shrunk Voronoi tessellations (Archives of Mechanics - Test, 2017)
Two-dimensional foam is a type of cellular solid materials containing a high volume fraction of pores. The thermal behavior of foam depends strongly on its microscopic structure. In this study, a two-dimensional closed-cell foam model containing randomly distributed air voids and solid walls is designed via a Voronoi diagram enhanced by the shrinking technique to approximately represent the real foam structure. The porosity, pore size and solid wall thickness of the established random foam structure is examined by introducing the so-called shrinking ratio. Subsequently, the effective thermal conductivity of the rebuilt foam model is numerically presented through the finite element analysis. The numerical results obtained are verified by comparison with the available theoretical and experimental results. In the analysis, the effects of porosity, number of pores and thermal conductivity of solid phase in foam structures are investigated respectively to reveal the relationship of geometric parameters and thermal properties of solid phase with effective thermal conductivity of the foam.